2007
DOI: 10.1074/jbc.m702066200
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Regulation of SecA

Abstract: In bacteria, the SecA protein associates with a ubiquitous protein channel SecYEG where it drives the post-translational secretion of pre-proteins across the plasma membrane. The high-resolution structures of both proteins have been determined in their resting states; however, the mechanism that couples ATP hydrolysis to active transport of substrate proteins through the membrane is not well understood. An analysis of the steady-state ATPase activity of the enzyme reveals that there is an allosteric binding si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…Some studies using deletion constructs suggested that the N-terminus is part of the SecA dimerization interface, 20,21,25,76,77 whereas others concluded the opposite. 78,79 To address this issue, we deleted residues 2–8, 2–9, and 2–10 (Δ2–8, Δ2–9, and Δ2–10, respectively) from wild-type SecA and examined the effects on dimerization. SecA dimerization affinity decreases with the number of residues deleted from the N-terminus (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies using deletion constructs suggested that the N-terminus is part of the SecA dimerization interface, 20,21,25,76,77 whereas others concluded the opposite. 78,79 To address this issue, we deleted residues 2–8, 2–9, and 2–10 (Δ2–8, Δ2–9, and Δ2–10, respectively) from wild-type SecA and examined the effects on dimerization. SecA dimerization affinity decreases with the number of residues deleted from the N-terminus (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Cloning, expression and purification of the translocation components and specific mutants thereof were conducted as described previously [9,23]. Reconstitution of SecYEG into total Escherichia coli polar lipids has been well documented [9].…”
Section: Methodsmentioning
confidence: 99%
“…Steady-state SecA ATPase measurements were monitored at 25 °C using a pyruvate kinase (PK)/lactate dehydrogenase (LDH)-coupled assay as previously described (18). Data were fitted to a one-site quadratic tight ligand-binding equation with background, Equation 1 defined as, where v is equal to enzyme velocity, B max is the total capacity of SecA-ligand, [ L ] is the total ligand ( i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Crystal structures have been obtained both for dimers of SecA (15) and for monomers of the enzyme (16), but dimers predominate in solution (17, 18). The structure of SecA bound to SecYEG in a 1:1 stoichiometry in the presence of an ATP analog (ADP-BeF x or ADP-AlF x ), reveals a major conformational change in the PPXD, which rotates away from the HWD to contact NBD2, in comparison with the structure of SecA alone (4).…”
Section: Introductionmentioning
confidence: 99%